PENGARUH LITERASI KEUANGAN, PENDAPATAN (UANG SAKU), DAN TEMAN SEBAYA TERHADAP PERILAKU KEUANGAN MAHASISWA MERCU BUANA YOGYAKARTA - Ekayuni Vitriani Hartati; Nugraeni Nugraeni (JURNAL ILMIAH EDUNOMIKA, 2026)
This study was conducted to determine and analyze the influence of financial literacy, income (pocket money), and peer influence on the financial behavior of Mercu Buana Yogyakarta students. The population in this study were all active students of Mercu Buana Yogyakarta University (UMBY) in the current academic year. The sampling technique used in this study was purposive sampling. The selected respondents were active students of Mercu Buana Yogyakarta University in at least their third semester, aged 18–25 years, and who regularly received pocket money from their parents, scholarships, or other sources of income. The data analysis technique used SPSS. The results of the study showed that financial literacy had a positive and significant effect on student financial behavior. Income (pocket money) had a positive and significant effect on student financial behavior. Peer influence had a positive and significant effect on student financial behavior. The data were declared normal, free from multicollinearity, and did not exhibit heteroscedasticity, so valid multiple linear regression analysis was used to draw conclusions in this study.